EDUKASI KESEHATAN BERBASIS VIDEO MOTION KONSUMSI REALFOOD MENINGKATKAN KEYAKINAN DIRI REMAJA OVERWEIGHT - Sinta Novia Dewi; Diana Tri Lestari; Yulisetyaningrum, Yulisetyaningrum (Nusantara Hasana Journal, 2025)
Self-confidence is one of the most important aspects of a person's personality, lack of self-confidence causes many problems for that person. Self-confidence among adolescents is related to external factors such as body weight. The tendency to gain weight can reduce adolescent self-confidence, especially when adolescents compare themselves to a good body image. In 2022, the problem of low self-confidence among adolescents in Indonesia was quite high, with the results of 15.5 million (34.9%) adolescents experiencing low self-confidence and 2.45 million (5.5%) adolescents experiencing mental disorders. Efforts that can be made to reduce the number of overweight in Indonesia include detecting cases of obesity as early as possible. The purpose of this study was to analyze the effect of education using motion video media on real food consumption on the self-confidence of the control group and the intervention group of overweight adolescents. The research design in this study used a Quasi-experiment. The time approach in this study used a cross-sectional approach. The independent variable in this study was the motion video of real food, while the dependent variable was the self-confidence of overweight adolescents. The location of the study was MA Sabilul Ulum Mayong. Based on the difference test of 2 unpaired groups using the Mann Whitney test, there was a P-value of 0.00, which means <0.05. So Ho is rejected and Ha is accepted, it can be concluded that there is a significant difference in changes in answers between the intervention group and the control group.